1974
DOI: 10.3758/bf03334234
|View full text |Cite
|
Sign up to set email alerts
|

Word length and exposure time effects on the recognition of bilaterally presented words

Abstract: Word length (two, three, four, and five letters) and exposure time (25, 50, and 100 msec) effects on visual half-field recognition performances were studied in a bilateral word presentation paradigm. Significant right-field recognition superiority (RFRS) obtained for all length-exposure time conditions except that for two-letter words exposed for 100 msec. RFRS was significantly greater for each of the two longer word lengths than for the two shorter lengths and for the 25-msec exposures than for the 50-or lOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Syllabicity has been shown to facilitate naming for difficult mono-and poly-syllabic words (e.g., Henderson, 1982;Taft, 1991). Length effects have been attested in both behavioural (Gill & McKeever, 1974;Lavidor & Ellis, 2002, among many others) and neurolinguistic studies (Cornelissen et al, 2003, Tarkiainen et al, 1999. The MEG literature, for example, typically shows detection of word-length effects around 150Á200 ms post-onset of visual word stimuli.…”
Section: Constraintsmentioning
confidence: 99%
“…Syllabicity has been shown to facilitate naming for difficult mono-and poly-syllabic words (e.g., Henderson, 1982;Taft, 1991). Length effects have been attested in both behavioural (Gill & McKeever, 1974;Lavidor & Ellis, 2002, among many others) and neurolinguistic studies (Cornelissen et al, 2003, Tarkiainen et al, 1999. The MEG literature, for example, typically shows detection of word-length effects around 150Á200 ms post-onset of visual word stimuli.…”
Section: Constraintsmentioning
confidence: 99%
“…(2) Parafoveal presentation sharply increases response latency (Eriksen & Schultz, 1977;Lefton & Haber, 1974). (3) Recognition scores decrease with increasing word length in the parafovea (Gill & McKeever, 1974;Schiepers, 1976b). (4) Response latencies for foveally presented single words do not show an influence of word length (Dogget & Richards, 1975;Johnson, 1975;Terry et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the past have reported an interaction between visual hemifield (VHF) and word length such that the number of letters in a word has a stronger effect in the left visual field (LVF) than in the right visual field (RVF) (e.g., Bouma, 1973;Gill & McKeever, 1974). However, these studies did not control some of the other properties of the stimulus materials that are known to be correlated with word length, such as the imageability of stimulus words (Young, Bion, & Ellis, 1980).…”
Section: Introductionmentioning
confidence: 99%